2014
DOI: 10.1186/1471-2458-14-911
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and smoking cessation: secondary analyses of a randomized controlled trial assessing physical activity as an aid for smoking cessation

Abstract: BackgroundSmokers have a lower body weight compared to non-smokers. Smoking cessation is associated with weight gain in most cases. A hormonal mechanism of action might be implicated in weight variations related to smoking, and leptin might be implicated. We made secondary analyses of an RCT, with a hypothesis-free exploratory approach to study the dynamic of leptin following smoking cessation.MethodsWe measured serum leptin levels among 271 sedentary smokers willing to quit who participated in a randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…The reduction in body weight is supported by previous studies that reported lower body weight among smokers compared to non-smokers and weight gain in most subjects who quit smoking [22] [23] [24]. Gonseth and his colleagues suggested a hormonal mechanism related to disturbed dynamics of leptin secretion after smoking cessation [25]. We found that co-exposure to nicotine and vitamin C failed to correct the nicotine-induced decrease in total body weight.…”
Section: Discussionsupporting
confidence: 73%
“…The reduction in body weight is supported by previous studies that reported lower body weight among smokers compared to non-smokers and weight gain in most subjects who quit smoking [22] [23] [24]. Gonseth and his colleagues suggested a hormonal mechanism related to disturbed dynamics of leptin secretion after smoking cessation [25]. We found that co-exposure to nicotine and vitamin C failed to correct the nicotine-induced decrease in total body weight.…”
Section: Discussionsupporting
confidence: 73%
“…A significant increase in serum leptin levels one year after smoking cessation was reported in a recent study by Gonseth et al [22].…”
Section: Discussionmentioning
confidence: 51%
“…Having in mind that hypadiponectinemia in overweight individuals and in type II diabetic patients is closely associated with insulin resistance and hyperinsulinemia [55], we excluded subjects with type II diabetes and severe obesity. Nevertheless, the lack of insulin data must be considered a limitation of our study since it has been suggested recently that insulin may be involved in the association of smoking and leptin [22]. Further research on this subject is needed.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Recently, some reports have linked leptin to tobacco craving and withdrawal-related symptoms. [19][20][21] Very few studies have examined leptin levels prospectively in accordance to the smoking habits in healthy individuals of both genders and in patients with COPD. In such a prospective study Lemieux A et al have found that leptin concentration en-hances during a period of 48 hours in females after quitting smoking, but remains stable in blood of non-smokers, in relapsers and in male abstainers.…”
Section: Discussionmentioning
confidence: 99%